(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This article discusses the basic knowledge and importance of Open Access platform and DOAB (Directory of Open Access Books). Open Access is simply the free online available of digital contents, scholarly journals articles, research results which authors publish without expectation of payment and is based on an ethical argument that research funded by the public should be available to the public. In the digital era Open Access movement is vastly expanded. The Open Access movement is growing fast in all direction overcoming the regional barriers and surpassing the disciplinary boundaries. Like journals, e-books also have been started to flourish in all fields of knowledge. The DOAB is a platform to have more visibility for open access books to the user communities.